The Influence of Lifestyle, Cashless Society and Residential Location on the Intention to Use QRIS as a Payment Tool - Rarawahyuni, Ika; Putri , Wulandari Eka; Sukarnoto, Toto; Paramole, Ibrahim Babatunde (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2025)
As the digital age progressed, several updated technologies were implemented, with the sole one affecting the incorrect payment method. People now choose to employ convenience while transacting with different types of matters. This research examines the effects of QRIS as a payment instrument on the Cirebon Regency community regarding their lifestyle choices, cashless society, and place of residence. This study utilises data from communities within the Cirebon Regency area. The research method employed is quantitative field research, which uses data analysis techniques, including instrument validity testing, reliability testing, classical assumption testing, hypothesis testing, and R-squared testing. The study results indicate that lifestyle variables negatively influence interest in QRIS usage. The calculated t-value of -5.092 is less than the critical value of -1.966, indicating that the cashless society variable positively affects interest when using QRIS. The calculated t value (28.967) exceeds the t table value (1.966), indicating that the variable location significantly negatively influences interest in using QRIS. The calculated t value is less than the critical value from the table (-5.211 < -1.966), indicating significance. Additionally, a third independent variable influences interest, with a QRIS of 72.6%. The calculated F value exceeds the critical F value (280.807 > 2.627), further supporting the findings. This study suggests that QRIS adoption strategies must focus on fostering cashless habits, overcoming geographic accessibility challenges, and enhancing financial literacy, particularly in rural regions characterised by high e-wallet usage and low banking penetration. The recommendation for research suggests that financial institutions implement educational programs focused on the responsible use of digital payments, enhance QRIS infrastructure in rural regions, prioritise practical benefits over lifestyle associations, and collaborate with e-wallet providers to address the needs of the 35% of unbanked users.